Alter Ego dalam Budaya Fandom (Studi pada Komunitas Penggemar Film Star Wars) - Ervando Baggio Riansyah (CommLine, 2015)
Film is a part of mass media. Film is a medium for entertainment yet give infor- mation for the audiences. As a mass media, film also give effects for the audiences, one of which is fanaticism. Cosplay is a form of fanaticism that is done by fans of a certain movie. Cosplay is an action of imitating characters from cartoons, comic books, or movies. In or- der to cosplay, fans can create their own alter egos and show it at certain moments. Alter ego is the other-self. This research aimed to acknowledge how the alter ego of fans which are members of the Star Wars fan communities was formed. The conceptual frameworks which been used in this research were Mass Media, the Mass Media Functions, Types of Massa Media, Film, Film Characteristics, Types of Movie, Movie Genres, Types of Movie’s Character, Culture, Fandom Culture, Alter Ego, Id, Ego & Superego, and Symbolic Interac- tionism. This research used constructivism paradigm with qualitative method. In-depth in- terview with purposive sampling as the method of selecting the informants. The informants are Star Wars fans and members of Star Wars fan communities. The informants also has their own alter egos. The result of this research shows that the fans wanted to feel as a part of Star Wars world with characters of their own creation. They are able to interact socially and comprehended the character of another human beings. The fans wanted to be a differ- ent character against their original. They created their own alter egos for their cosplay.